Renewable and eco-friendly ZnO immobilized onto dead sea sponge floating materials with dual practical aspects for enhanced photocatalysis and disinfection applications. (15th January 2023) - Bhatti, Muhammad Ali; Almani, Khalida Faryal; Shah, Aqeel Ahmed; Tahira, Aneela; Chana, Iftikhar Ahmed; Aftab, Umair; Ibupoto, Mazhar Hussain; Mirjat, Abdul Nabi; Aboelmaaref, Amal; Nafady, Ayman; Vigolo, Brigitte; Ibupoto, Zafar Hussain
Abstract: In this study, we have investigated the role of natural dead sea sponge (DSS, Porifera) as a three-dimensional (3D) porous host substrate for the immobilization of nanostructured ZnO material towards the development of ZnO based floating photocatalysts for efficient removal of methylene blue (MB) dye under the illumination of sunlight. After photodegradation, the treated water after dye degradation contains several pathogens, different disinfectants or chemical reagents that are essentially used. This is not the case for DSS as it can naturally kill any pathogens during the wastewater treatment process. To explore these functions, ZnO nanosheets were incorporated onto DSS via hydrothermal protocol and the as prepared ZnO/DSS hybrid material exhibited approximately ∼100% degradation efficiency for the removal of MB. Importantly, the degradation kinetics associated with the fabricated ZnO/DSS was remarkably accelerated as evidenced by the high values of degradation reaction rate constants (3.35 × 10 –2 min −1 ). The outperformance of ZnO/DSS could be attributed to the adsorption caused by its 3D porous structure together with the high rapid oxidation of MB. Furthermore, the high charge separation of electron–hole pairs, natural porosity, and abundant catalytic sites offered by the hybrid ZnO/DSS floating photocatalyst have enabled quantitative (∼100%) degradation efficiency for MB. Finally, the excellent reusability results confirm the feasibility of using natural ZnO/DSS-based photocatalyst for practical solution of wastewater treatment and other environmental problems.